Linha motriz - Andrade, Louise dos Reis Gusmão (2023)
Linha Motriz is an artistic project, in the line of creative processes in visual arts, equivalent to a master's thesis, composed mainly by works that have textile art as visual poetic. This is the elaboration of an academic research that highlights the development and deepening of my authorial artistic research, covering the requirements and demands of the research process in visual poetics, promoting the textures that generated, together with the practice, the critical reflections , records and theoretical studies intertwined in this investigation. In this way, I share here, in a personal and first-person narrative, the paths, the tests and references from which derive the meanings and the interweaving that weave this plot, sewn by the crossings of this "political-affective" territory, germinated between the poetic process of making embroidery and the role of contemporary textile art as a means of reappropriating women's social and political space.